The effects of delayed tracking: Evidence from German states - Simon Lange; Marten von Werder (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2014)
Germany's education system stands out among OECD countries for early tracking: students are tracked into different secondary school types at the age of ten in most German states. In this paper we estimate the effects on educational outcomes of a reform that delayed tracking by two years. While our findings suggest that the reform had no effect on educational outcomes on average, we find a positive effect on male students with uneducated parents and a negative effect on males with educated parents. The reform thus increased equality of opportunity among males, yet not among females. We argue that the gendered pattern is best explained by developmental differences between boys and girls at the relevant age.
Keywords: I21; I24; I28; J62; 330; tracking; educational institutions; intergenerational mobility